2017
DOI: 10.1111/jgs.15031
|View full text |Cite
|
Sign up to set email alerts
|

Global Sensory Impairment Predicts Morbidity and Mortality in Older U.S. Adults

Abstract: OBJECTIVES:To evaluate global sensory impairment (GSI, an integrated measure of sensory dysfunction) as a predictor of physical function, cognition, overall health, and mortality. DESIGN: Prospective study. SETTING: The National Social Life, Health, and Aging Project. PARTICIPANTS: A national probability sample of 3,005 home-dwelling older U.S. adults assessed at baseline and 5-year follow-up (2010-11). MEASUREMENTS: Gait speed, activity, disability, cognition, overall health, 5-year mortality. RESULTS: At ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 55 publications
(92 reference statements)
3
48
1
Order By: Relevance
“…Among the mortality studies, controlling for performance in activities of daily living or frailty score did not attenuate the effect (Pinto et al, 2014;Schubert et al, 2016). Global sensory impairment (including the five classical senses: smell, taste, hearing, vision and touch) predicts 5-year mortality, but also major components of physical frailty (e.g., slow gait, weight loss, low activity) (Pinto et al, 2017). The same authors developed the concept that multisensory loss of function could reflect a common underlying aging process (Correia et al, 2016).…”
Section: Accelerated Brain Agingmentioning
confidence: 86%
“…Among the mortality studies, controlling for performance in activities of daily living or frailty score did not attenuate the effect (Pinto et al, 2014;Schubert et al, 2016). Global sensory impairment (including the five classical senses: smell, taste, hearing, vision and touch) predicts 5-year mortality, but also major components of physical frailty (e.g., slow gait, weight loss, low activity) (Pinto et al, 2017). The same authors developed the concept that multisensory loss of function could reflect a common underlying aging process (Correia et al, 2016).…”
Section: Accelerated Brain Agingmentioning
confidence: 86%
“…First, even if analyses of the potential impact of attrition revealed no major differences in the main results, the fact that those who were lost to follow-up were more likely to be older, female and low educated might have led to underestimating the DA index slope. Another limitation is that, despite our study included a greater number of health deficits than most previous reports [3;4;6;8], it did not include sensory impairments, which are highly prevalent and have shown to predict mortality in older adults [30]. Also, although adjustment for functionality was performed, results for dimensions that relied on self-reported data (i.e.…”
Section: Discussionmentioning
confidence: 96%
“…They measured sensitivity thresholds for taste, smell, thermal sensitivity (cooling), vibrotaction (both low- and high-frequency), and hearing (both low- and high-frequency) in 15 young and 22 older participants and observed an age-related reduction in sensitivity and acuity. The authors found significant positive correlations between all the modalities and age accounted for most of the variance challenging the “common factor theory” (or global sensory impairment) which instead postulates that common mechanisms underlie the decline of the sensory systems, supporting the concept of a unified underlying process of sensory aging [ 20 , 24 ]. Such a framework is conceptually similar to the concept of the “common cause hypothesis”, which states that a common underlying factor drives age-related deterioration in cognitive and sensory processes [ 23 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%